Osmoregulation and muscle water control in vitro facing salinity stress of the Amazon fish Oscar Astronotus ocellatus (Cichlidae). Issue 4 (4th July 2017) - Gutierre, Silvia M. M.; Schulte, Jessica M.; Schofield, Pamela J.; Prodocimo, Viviane
Abstract: Specimens of Oscar Astronotus ocellatus from a fish farm were abruptly submitted to salt stress of 14 ppt and 20 ppt, for 3 and 8 h to determine their plasma osmolality. Muscle wet body mass change in vitro was analyzed from control freshwater animals. Fish in 14 ppt presented no osmolality distress even after 8 h. In 20 ppt, a slight increase (10%) in plasma osmolality was observed for both times of exposure when compared to control fish. Muscle slices submitted in vitro to hyper-osmotic saline displayed decreased body mass after 75 min, and slices submitted to hypo-osmotic saline displayed increased body mass after 45 min when compared to control (isosmotic saline). These results reinforce A. ocellatus 's euryhalinity. The fish were able to regulate its internal medium and tolerate 14 ppt, but presented an intense osmotic challenge and low muscle hydration control when facing salinities of 20 ppt.